Photography and Tourism Potential of Denai Kuala Village - Agung Suharyanto; Rehia K. Isabella Barus; Bebby Masitho Batubara (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
Denai Kuala Village, a coastal village, is a destination for developing photo tourism potential by utilizing natural conditions that are still natural, located in Pantai Labu District, Deli Serdang. Geographical conditions that are still natural, can still be developed as a tourist destination, although demographically it is very possible urbanization. This becomes necessary to get its own attention, because of this condition, one of the solutions is to provide science and technology to the community in order to develop the natural, cultural, and Human Resources potential that is available to increase people's income. If the welfare of the community increases, it will automatically reduce the level of urbanization. In fact, if the growth is significant enough, urban people will flock back to the village and advance their homeland. Based on the results of discussions with the Medan Area University PKM implementation team with the Indonesian Women's Union (SPI) as partners, the problem resolution will be done based on priority scale. Concretely the solution to the problem is: 1) Mapping the tourist area by choosing interesting photo spots for photography; 2) Conducting Training and Website Creation of Denai Kuala Village regarding interesting photo spots for photography and utilizing social media for promotion tools on the internet. From the beach site, grass fields, fish drying fields, rivers, ships and bridges, (landscape), mangrove forests and pine forests, has its own uniqueness if processed into its own tourism potential. Some elements of nature du top, can be made one model for specific spots in areas that are in accordance with the aesthetic of photography. These angles are taken with a photo camera. These results are then disseminated to residents, especially and training to residents, especially female kaun, to recognize site specific photography in Denai Kuala Village, as a tourism potential. Photo documentation obtained, then selected into materials to be marketed for solutions to problems in the field of marketing. These materials are made on the website to utilize social media for promotion tools on blogspot.